1993
DOI: 10.1039/p29930001269
|View full text |Cite
|
Sign up to set email alerts
|

Models for nuclease catalysis: mechanisms for general acid catalysis of the rapid intramolecular displacement of methoxide from a phosphate diester

Abstract: The dianion of the dialkyl phosphate diester 3 is hydrolysed in water at 50 "C with a half-life of less than 2 min. The reaction involves highly efficient intramolecular nucleophilic catalysis (effective molarity mol dm-3) by the phenol OH over the whole pH range. The initial products are the cyclic phosphate diester and methanol: no phosphate migration is observed. General acid catalysis is observed for the reactions of all ionic species, and has been characterised in detail for the monoand di-anion. An impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 23 publications
2
46
0
Order By: Relevance
“…Ϫ All starting materials (2a, 2b, 2c, 2d, 2e, 7) are commercially available and were used without further purification. Compound 2f [26] was synthesized according to the literature procedure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ϫ All starting materials (2a, 2b, 2c, 2d, 2e, 7) are commercially available and were used without further purification. Compound 2f [26] was synthesized according to the literature procedure.…”
Section: Methodsmentioning
confidence: 99%
“…2-Bromophenol was protected as the benzyl ether [26] and subjected to the reaction sequence with acetonitrile and iodine to give iodo ketone 3f in good yield.…”
Section: Scheme 2 Synthesis Of Chiral Hypervalent Iodine Compound 1kmentioning
confidence: 99%
“…It has been shown that the ␤ lg for a series of aryl-phosphate diester compounds is even less negative (␤ lg ϭ Ϫ0.2) in the active site of RNase A, suggesting a considerable contribution of electrophilic catalysis in the active site (33). Brønsted analysis using aryl-phosphate diester compounds gave a Brønsted coefficient, ␤, of 0.67 (␣ of 0.33) (32,34). In the study presented here, a Brønsted coefficient was obtained by using a natural RNA phosphodiester as the substrate: for a mechanism of general base catalysis, ␤ is 0.51, or for the kinetically equivalent mechanism, specific base͞general acid catalysis, ␣ is 0.49.…”
Section: Discussionmentioning
confidence: 99%
“…In 3.25 [55] (Scheme 2.28) a highly efficient nucleophilic reaction ðEM > 10 10 Þ supports the general acid catalyzed displacement of methoxide as methanol. Two model systems illustrate the potential of such effects.…”
Section: Scheme 226mentioning
confidence: 86%